Faktor - Faktor Yang Mempengaruhi Perilaku Menabung Pada Mahasiswa Program Studi Pendidikan Ekonomi Universitas PGRI Ronggolawe Tuban - Puspitasari, Jupita; Habib, Muhammad Khoirul; Widrayadi, Yosia Dian Purnama (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the influence of financial literacy, self-control, parental influence, peer influence, and income on students’ saving behavior in the Economic Education Study Program at Universitas PGRI Ronggolawe Tuban for the 2021–2024 cohort. A quantitative approach with an associative research design was applied. The population consisted of 173 students, and the sample was determined using Slovin’s formula with a total of 64 respondents. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS, including classical assumption tests. The results reveal that financial literacy, parental influence, and income have a significant positive effect on saving behavior, while self-control and peer influence have a significant negative effect. The coefficient of determination (R²) is 0.724, indicating that 72.4% of the variation in students’ saving behavior can be explained by the independent variables, while the remaining 27.6% is influenced by other factors outside the model. These findings highlight that students’ saving behavior is shaped by the interplay of cognitive, psychological, social, and economic factors.